Investigation of relationships between fecal contamination, cattle grazing, human recreation, and microbial source tracking markers in a mixed-land-use rangeland watershed. (15th April 2021) - Joseph, Naveen; Lucas, Jane; Viswanath, Nikhil; Findlay, Reed; Sprinkle, Jim; Strickland, Michael S.; Winford, Eric; Kolok, Alan S.
Highlights: MST coupled with E. coli measurements quantifies fecal contamination effectively. A mixed-effects regression model was developed and validated for E. coli estimation. E. coli and dissolved oxygen holds a strong inverse relationship in Mink Creek. E. coli was primarily contributed by human (58.8%) and unknown (29.4%) sources. Abstract: The United States National Forests are mixed-use lands that support human recreation and cattle grazing. Overuse by humans or cattle, however, can lead to the fecal contamination of local waterways. Until recently, the source of these contaminants was a subject of conjecture; however, microbial source tracking tools have become widely used and are proving to be a valid methodology to identify the contamination source. This study aims to analyze and model the quantity and sources of fecal contamination in the Mink Creek watershed in southeastern Idaho. The U.S. Forest Service Caribou-Targhee National Forest (USFS) manages this watershed. Previous research has indicated that some localities within the watershed exceed US EPA standards for coliform bacteria. In 2019, water samples were collected before livestock began grazing and throughout the spring, summer, and fall after livestock grazing had ended. Fourteen sites were sampled seven times during the field season, allowing the water to be analyzed for total coliforms and E. coli bacteria. Microbial source tracking techniques using Bacteroides bacteria, which are known to live in specific digestive tracks, were used to identify the source of E. coli at each sampling location. The analysis indicated that E. coli counts exceeded state regulatory limits 35% of the time. These exceedances were associated with DNA source tracking markers for humans (58.8%), cattle (5.9%), or both cattle and humans (5.9%). Unknown sources were responsible for the Bacteroides bacteria 29.4% of the time. A statistical model was developed to estimate E. coli using the datasets of microbial source tracking measures, the presence or absence of humans, cattle, the proximity of the sampling date to a holiday, and other seasonal factors. The resulting model showed good performance indices at all the 14 sites based on a K-fold cross-validation scheme (R 2  = 0.83 and NSE = 0.69). The results demonstrated that E. coli exceedances have a close association with human recreation and unknown sources and negatively influenced by dissolved oxygen. Graphical abstract: Image, graphical abstract